The Cash Dividend : the Rise of Cash Transfer Programs in Sub-Saharan Africa - Garcia, Marito, 1951- (Directions in development (Washington, D.C.). Human development., 2012)
The Cash Dividend: The Rise of Cash Transfer Programs in Sub-Saharan Africa assimilates results of a thorough review of the recent use of cash transfer programs in Sub-Saharan Africa. Drawing from sources including program documentation, policy papers, peer-reviewed publications, and interviews, it paints a picture of the evolution and current state of cash transfers, which include unconditional and conditional cash transfers and emergency- and development-focused transfers. It presents analysis from data collected and describes broad trends in design features and implementation, including objectives, targeting, benefits, payment mechanisms, conditions, monitoring, evaluation, institutional location, program costs, and more. It also addresses political economy issues relevant to cash transfer programs, discusses the challenges to implementing cash transfer programs in Sub-Saharan Africa, and highlights lessons learned from existing African cash transfer programs. The comprehensive nature of the review, and its thorough analysis of previously unassimilated data, fills a gap in knowledge related to cash transfer programs in the region. The book is expected to benefit the donor community and domestic policymakers involved in cash transfers in Sub-Saharan Africa, guiding both program design and future research. It will help shift the debate on cash transfers in Africa from whether they are possible to how they can best be implemented.